Pengaruh Job Characteristics Terhadap Job satisfaction Melalui Employee Engagement Pada Karyawan PT. Sucofindo Cabang Utama Surabaya - Angga, Moch. Nur; Budiono (Jurnal Ilmu Manajemen, 2024)
The study discusses job characteristics, job satisfaction and employee engagement. In this case, job characteristics and employee engagement must be able to run well so that satisfaction in PT. X employees can be consistent and increase. This study aims to test and analyse the effect of job characteristics on job satisfaction through employee engagement in PT. X employees. This research is causal and uses a quantitative approach involving all PT employees. X. The sampling technique uses non-probability sampling with a saturated sample type in which all population members are sampled with a total of 99 respondents of the PT. X employees. The statistical analysis used in this research is Structural Equation Modeling SEM with the help of Smart Partial Least Square (PLS) software version 4.1.0.1. using a sample of 99 respondents. The analysis results obtained in this study indicate that job characteristics positively and significantly affect job satisfaction. Job characteristics have a positive and significant effect on employee engagement. Employee engagement has a positive and significant effect on job satisfaction. Employee engagement can mediate the relationship between job characteristics and job satisfaction. The practical implication of this study is that PT. X needs to continue to improve employee satisfaction by improving job characteristics and increasing their engagement. This is expected to increase the comfort and enthusiasm of employees in their work.